Autoimmunity Features in Patients With Non-Celiac Wheat Sensitivity. (25th May 2021) - Mansueto, Pasquale; Soresi, Maurizio; Candore, Giuseppina; Garlisi, Chiara; Fayer, Francesca; Gambino, Caterina Maria; La Blasca, Francesco; Seidita, Aurelio; D'Alcamo, Alberto; Lo Sasso, Bruna; Florena, Ada Maria; Geraci, Girolamo; et al.
Abstract : INTRODUCTION: Nonceliac wheat sensitivity (NCWS) is characterized by intestinal and extraintestinal manifestations consequent to wheat ingestion in subjects without celiac disease and wheat allergy. Few studies investigated the relationship between NCWS and autoimmunity. The aim of this study is to evaluate the frequency of autoimmune diseases (ADs) and autoantibodies in patients with NCWS. METHODS: Ninety-one patients (13 men and 78 women; mean age of 40.9 years) with NCWS, recruited in a single center, were included. Seventy-six healthy blood donors (HBD) and 55 patients with a diagnosis of irritable bowel syndrome (IBS) unrelated to NCWS served as controls. Autoantibodies levels were measured. Human leukocyte antigen haplotypes were determined, and duodenal histology performed in all patients carrying the DQ2/DQ8 haplotypes. Participants completed a questionnaire, and their medical records were reviewed to identify those with ADs. RESULTS: Twenty-three patients with NCWS (25.3%) presented with ADs; autoimmune thyroiditis (16 patients, 17.6%) was the most frequent. The frequency of ADs was higher in patients with NCWS than in HBD ( P = 0.002) and in patients with IBS ( P = 0.05). In the NCWS group, antinuclear antibodies tested positive in 71.4% vs HBD 19.7%, and vs patients with IBS 21.8% ( P < 0.0001 for both). The frequency of extractable nuclear antigen antibody (ENA) positivity was significantly higher in patients with NCWS (21.9%) than in HBD (0%) and patients with IBS (3.6%) ( P = 0.0001 and P = 0.004, respectively). Among the patients with NCWS, 9.9% tested positive for antithyroglobulin, 16.5% for antithyroid peroxidase, and 14.3% for antiparietal cell antibodies; frequencies were not statistically different from controls. The presence of ADs was related to older age at NCWS diagnosis, female sex, duodenal lymphocytosis, and eosinophil infiltration. DISCUSSION: One in 4 patients with NCWS suffered from AD, and serum antinuclear antibodies were positive in a very high percentage of cases. These data led us to consider NCWS to be associated to ADs.